Droplet impact of blood and blood simulants on a solid surface: Effect of the deformability of red blood cells and the elasticity of plasma. (February 2022) - Yokoyama, Yuto; Tanaka, Akane; Tagawa, Yoshiyuki
Highlights: Comparison on droplet impacts of blood and suspensions with similar viscosity. Suspensions used include plasma with particles and commercial blood simulant (BS). Droplets of BS spread or splash differently from blood. It is highly recommended to use deformable particles in BS. Graphical Abstract: ga1 Abstract: The impact of blood droplets onto a solid wall is of great importance for bloodstain pattern analysis in forensic science. Previous studies suggest that the behaviour of impacting blood is similar to that of a Newtonian fluid, which has a shear viscosity equivalent to that of blood at high shear rates. To understand this important fact, we conducted comparative experiments of droplet impact on a glass surface using whole blood and three solutions with a shear viscosity similar to that of blood. Specifically, we used dog's whole blood (deformable red blood cells dispersed in plasma, WB), plasma with non-deformable resin particles (PwP), glycerol and water with resin particles (GWwP), and a commercial blood simulant (hard particles dispersed in a water-based Newtonian solution, BS). Ranges of Reynolds and Weber numbers in our experiments were 550< Re <1700 and 120< We <860, respectively. Side and bottom views of droplet impact were simultaneously recorded by two high-speed cameras. The spreading radius of the impacting WB droplet in our experiments agreed well with that of Newtonian fluids with viscosity similar to that of WB at high shear rates. Splashing droplets of WB and Newtonian fluids form finger structures (finger-splashing). Although PwP has a viscosity similar to that of WB at high shear rates, an impacting PwP droplet exhibited typical characteristics of impacting suspension droplets, that is, a reduced spreading radius and splashing with ejection of particles. Such significant differences between impacting droplets of PwP and WB indicates that the high deformability of red blood cells in WB plays a crucial role in the Newtonian-like behaviour of blood droplets on impact. The finger-splashing of PwP and GWwP exhibited no significant difference, indicating that the effect of plasma elasticity on finger-splashing is negligible. Importantly, the impacting BS droplet behaved quite differently from WB in both spreading and splashing. Our results imply that the use of deformable particles rather than hard particles in a BS is essential for mimicking blood droplet impact.